The feeding habits of gafftopsail catfish Bagre marinus (Ariidae) in Paraiso Coast,Tabasco, Mexico - Mendoza-Carranza, Manuel (HIDROBIOLÓGICA, 2017)
The gafftopsail catfish (Bagre marinus) is one of the species of most importance to fisheries in the Gulf of Mexico, particularly in the coastal region of Tabasco State, where it is captured abundantly almost all year round in shallow coastal zones. Although, there is neither ecological nor biological information about this species in the coastal zone of Tabasco State. This study aims to describe the feeding habits of gafftopsail catfish. Seasonal changes in the diet and its relation with reproductive period will also be discussed. Analyzes of stomachs contents of 430 individuals (97 females and 68 males for dry season, 100 females and 38 males for rainy season and 83 females and 44 males for nortes season) obtained from two commercial landings located in the Chiltepec municipality, Paraiso, Tabasco along one year (May 1996 to April 1997). The numerical percentage (%N), weight percentage (%W) and frequency occurrence indexes were calculated for the groups preys. These three indexes were comparing with the Kendall concordance coefficient, concluding that three indexes provide the same information about importance of prey inside diet, using the %F for posteriors analysis. Brachyurans were the more important preys inside the annual diet of species, reached a maximum frequency of occurrence during dry season (74.6 %F for females and 92.7 %F for males). Few seasonal changes in diet of both sexes were observed, with a progressive increase of occurrence of fishes and diminution of stomatopods and penaeid shrimps. No significant differences were finding in total diet between females and males. The variation of the proportion of fullness stomachs and fullness weight index along the year can be related with the reproductive behavior of species.